Implementation of Islamic Education in Strengthening the Social Care Character of Students at Madrasah Aliyah - Subaidi Subaidi; Nunu Mahnun; Junaidi Arsyad (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study examines the role of Islamic education at Madrasah Aliyah Amsilati Bangsri Jepara in cultivating students' care character. It aims to provide an in-depth understanding of the educational programs that contribute to developing this vital character trait among students. A descriptive qualitative methodology was employed to observe the implementation of various educational programs at the institution. The participants included students across all grades. Data were collected through observations, interviews, and document analysis, and analyzed through a three-stage process: reduction, presentation, and conclusion drawing. The study identified eight principal programs that effectively foster the care character among students. These programs include community service initiatives, educational support activities, and other projects that promote the sharing of material resources and knowledge. The findings indicate that these programs significantly enhance the character of social care among students. By participating in these initiatives, students develop a sense of responsibility and empathy, which are crucial components of the care character. Islamic education at Madrasah Aliyah Amsilati Bangsri Jepara plays a significant role in strengthening the care character of students through well-structured educational programs. This study highlights the importance of incorporating such programs in educational curricula to nurture socially responsible individuals.